Perancangan Alat Monitoring Kualitas Tanah Tanaman Kedelai Berbasis Internet Of Things - Purwanto, Muhamad Dendi; Sujadi, Harun; Marina, Ida (Universitas Multi Data Palembang, 2024)
The aim of this research is to create a device that can track the health of soybeans and plant watering in real time using soil moisture and nutrients in the soil in the village of Babakanmanjeti. How efficient and durable this tool is currently being used in soya fields will be studied further through this research. The device is excellent for monitoring soil humidity and soil pH of soybean crops and displaying those values through the Arduino Cloud software located on the smartphone. If the soil humidity is higher than the specified value, i.e. 250, and more than 75%, the pump test will start automatically. Conversely, if the moisture level is less than the specific value, that is, 467, and less than 60%, the test of the pump will be activated automaticly.